A High Vitamin C Micronutrient Supplement Is Unable to Attenuate Inflammation in People with Metabolic Syndrome but May Improve Metabolic Health Indices: A Randomised Controlled Trial - Emma Vlasiuk; Masuma Zawari; Rebekah Whitehead; Jonathan Williman; Anitra C. Carr (MDPI AG, 2024)
Chronic low-grade inflammation is a characteristic of people with metabolic syndrome and is thought to contribute to the condition progressing to the more severe type 2 diabetes and cardiovascular disease (CVD). The aim was to carry out a double-blind randomised placebo-controlled trial in people with metabolic syndrome to determine if supplementation with a micronutrient formula containing 1000 mg/d vitamin C could attenuate inflammation in people with metabolic syndrome. We recruited 72 adults aged a median of 52 years with metabolic syndrome, defined as obesity (based on waist circumference or BMI), and at least two of hyperglycaemia, raised triglycerides, lowered HDL cholesterol, hypertension, or taking medications for these conditions. A further inclusion criteria comprised C-reactive protein (CRP) concentrations ≥ 3 mg/L, i.e., high risk of CVD. The participants were randomised to daily micronutrient formula (n = 37) or matched placebo control (n = 35) for 12 weeks. The primary outcome was change in CRP concentrations and secondary outcomes included changes in vitamin C concentrations, pro-inflammatory cytokines (IL-6, TNFα), oxidative stress marker (F2isoprostanes), glycaemic indices (glucose, insulin, HbA1c), lipid markers (triglycerides, LDL and HDL cholesterol), anthropometric parameters (weight, BMI), insulin resistance and insulin sensitivity, and metabolic severity score. The participants had a low median (Q1, Q3) vitamin C status of 29 (15, 41) µmol/L and a high proportion of hypovitaminosis C (38%) and outright deficiency (19%). Following 12 weeks of micronutrient supplementation, at least 70% of the participants reached adequate vitamin C status (≥50 µmol/L), however, there was no change in CRP concentrations relative to the placebo group (Δ−0.3 [95%CI −2.7, 2.1] mg/L, p = 0.8). Similar trends were observed for IL-6, TNFα and F2isoprostanes (p > 0.05). Instead, there were small improvements in BMI, fasting glucose and HbA1c concentrations, insulin sensitivity and metabolic severity score in the micronutrient group relative to placebo (p < 0.05). Overall, 12-week micronutrient supplementation was unable to mitigate systemic inflammation in people with metabolic syndrome but may improve several metabolic health indices.